As tecnologias de informação e comunicação em cursos de licenciaturas em matemática - Souza, Jediane Teixeira de (2008)
It s easy to realize the big difficulty that the Mathematics teacher have to deal with the new thecnologic in the base education. Although these thecnologics beeing around us the teaching is still restrict to the blackboard and the chalk and many teacher don t use them. One of the reasons is the lack of knoledge. In this way investigate in what conditions the inicial formation courses apply the activities as in the thecnical meanning of thecnology and softwares as in the way that these tools can be used in the classroom are points to be discussed and researched. The goal of this research is to investigate superior teaching institutes that offer teaching Mathematics courses reliable to thecnological resources, oportunities of digital inclusion and the preparation of future Mathematics teachers to use the TIC as a pedagogical resorce.It was made interviews with two teachers that use the thecnologies in their classes and two coorditators of private institutions, na University and a College isolated. It was also made a documental analyses of the Pedagogical Projects of the teaching Mathematics courses as well the memmorandum book of the two institutions that referer the use of new thecnology. The results show that the two institutions offer material and thecnological resources. The University course offers subjects in the area of Information and Computation in order to instruct the student about the computer s components working and the existence of the aplication of the basic tools of computation, and the subject Information in Education to touch the future teachers about the importancy of information to develop many humans abilities and give practical experience to make a class plan that uses the computer as a thecnological resouce. The College course offers subjects of mathematics formation that use the TIC as educational tool, in order to use the TICs as pedagogical resouce to build the geometrical knoledge and graphics. Althoug there isn t subjects characterized like Information in Education, some Mathematics subjects offer moments of investigation of the TIC applied to the Education by the reading of articles that enfasesing the vantages and advantages of the using of softawares to guide the teachers in how to use the thecnologies in the teaching prectice. However, there is a quetionament if it s enough to offer the thecnological resources and subjects about the mentioned categories to permit the teachers to use the thecnologies in a pedagogical manner